Antirealist escape to the realm of possibilities - Wójtowicz, Krzysztof (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2008)
The article is devoted to a popular presentation of two important styles of thinking concerning the problem of existence of mathematical objects: Chihara’s linguistic constructivism, and Hellman’s modal structuralism. According to Chihara, mathematical statements should be interpreted as referring to certain linguistic construction; according to Hellman, mathematics is the science of possible structures. The motivations and main ideas are examined (without going into technical details), and the similarities and differences between these two viewpoints are highlighted.